Electron driven water formation from oxyhydrogen clusters in superfluid helium nanodroplets. (August 2015) - Renzler, Michael; Kranabetter, Lorenz; Barwa, Erik; Illenberger, Eugen; Scheier, Paul
Synopsis: Helium nanodroplets provide an enviroment that allow studies of chemical reactions at ultracold temperatures. We use these droplets as a matrix to study the formation of water upon electron bombardment of oxyhydrogen clusters